54‐3: Distinguished Paper: High Temperature Thin‐Film Barriers for Foldable AMOLED Displays. Issue 1 (30th May 2018) - Akkerman, Hylke; Pendyala, Raghu; Panditha, Pradeep; Salem, Ahmed; Shen, Jie; van de Weijer, Peter; Bouten, Piet; de Winter, Suzanne; van Diesen-Tempelaars, Karin; de Haas, Gerard; Steudel, Soeren; Huang, Ching-Yu; et al.
Abstract : We present a thin‐film dual‐layer bottom barrier on PI that is compatible with 350°C backplane processing for OLED displays. We demonstrate OLEDs that survive bending over 0.5 mm radius for 10.000x. Furthermore, we show compatibility of the bottom barrier with the backplane process by fabricating AMOLED displays on GEN1‐sized substrates.